Detecting Cortical Spreading Depolarization with Full Band Scalp Electroencephalography: An Illusion? - Hofmeijer, Jeannette; van Kaam, C. R.; van de Werff, Babette; Vermeer, Sarah E.; Tjepkema-Cloostermans, Marleen C.; van Putten, Michel J. A. M. (Frontiers in Neurology, 2018)
Introduction There is strong evidence suggesting detrimental effects of cortical spreading depolarization (CSD) in patients with acute ischemic stroke and severe traumatic brain injury. Previous studies implicated scalp EEG features to be correlates of CSD based on retrospective analysis of EEG epochs after having detected ‘CSD’ in time aligned electrocorticography. We studied the feasibility of CSD detection in a prospective cohort study with continuous EEG in 18 patients with acute ischemic stroke and 18 with acute severe traumatic brain injury. Methods Full band EEG with twenty-one silver/silver chloride electrodes was started within 48 hours since symptom onset. Five additional electrodes were used above the infarct. We visually analyzed all raw EEG data in epochs of one hour. Inspection was directed at detection of the typical combination of CSD characteristics, i.e. (i) a large slow potential change accompanied by a simultaneous amplitude depression of >1Hz activity, (ii) focal presentation, and (iii) spread reflected as appearance on neighboring electrodes with a delay. Results In 3035 one hour EEG epochs, infraslow activity (ISA) was present in half to three quarters of the registration time. Typically, activity was intermittent with amplitudes of 40-220μV, approximately half was oscillatory. There was no specific spatial distribution. Relevant changes of ISA were always visible in multiple electrodes, and not focal, as expected in CSD. ISA appearing as ‘slow potential change’ was mostly associated with an amplitude increase of faster activities, and never with suppression. In all patients, depressions of spontaneous brain activity occurred. However, these were not accompanied by simultaneous slow potential change, occurred simultaneously on all channels, and were not focal, let alone spread, as expected in CSD. Conclusion With full band scalp EEG in patients with cortical ischemic stroke or traumatic brain injury, we observed a variety of ISA, probably modulating cortical excitability. However, we were unable to identify unambiguous characteristics of CSD.